The The Impact of Digital Transformation on Partnership Performance – The Mediating Effect of Service Innovation - Nushobah, Ahmad Royan; Sumiati; Kusuma Ratnawati (Profesional Muda Cendekia Publishing, 2023)
This study investigates the influence of digital transformation and service innovation on the partnerships performance in state revenue management in Indonesia. The study's population encompasses 95 organizations that collaborate with the Ministry of Finance in collecting state revenues. Employing a quantitative approach, the study utilizes explanatory research and gathers data through questionnaires distributed to 95 managers from various organizations. Structural equation modelling and partial least squares with SmartPLS software were employed for data analysis. The findings indicate that both digital transformation and service innovation have a significant positive impact on partnership performance. Notably, service innovation acts as a mediating variable in the relationship between digital transformation and partnership performance. These results suggest that organizations should integrate digital transformation into their service innovation strategies to achieve the desired partnership performance.